Selectivity of insecticides to three vespidae predators of Dione juno juno (Lepidoptera: Heliconidae) - Moura, Marcelo Fialho de; Picanço, Marcelo; Gonring, Alfredo Henrique Rocha; Bruckner, Cláudio Horst (Pesquisa Agropecuaria Brasileira, 2000)
Among insects that attack passion fruit, Dione juno juno (Lepidoptera: Heliconidae) is considered the most dangerous plague. The selectivity of the insecticides fenthion, cartap, malathion and deltamethrin to the predatory wasps Polybia fastidiosuscula, Polybia scutellaris and Protonectarina sylveirae (Hymenoptera: Vespidae) was studied based on these insecticide toxicities to their prey Dione juno juno. Concentration-mortality regression lines were obtained and the estimated lethal concentration of insecticide to 90% (LC90) of the individuals were used for the calculation of the differential selectivity index and tolerance index. Deltamethrin was selective in favor of P. scutellaris and P. fastidiosuscula and showed intermediate selectivity to P. sylveirae, while cartap showed intermediate selectivity to all three species of predatory wasps. Malathion was selectivite to P. sylveirae and showed intermediate selectivity to P. fastidiosuscula. The predatory wasps P. sylveirae and P. fastidiosuscula were more tolerant to cartap than P. scutellaris and P. sylveirae was more tolerant to malathion than P. fastidiosuscula and P. scutellaris.